Fabrication on antireflection-structured film by ultraviolet nanoimprint lithography and its mold lifetime amelioration - Nurhafizah, Abu Talip (2016)
Antireflection (AR) nanostructures from biomimetic moth-eye structures which can eliminate the undesirable reflection and increase the light transmission on the film surface have various applications in micro-nano discipline and nanophotonics fields. The significant applications of AR nanostructures ranging from improving the visibility of flat panel displays (FPDs), enhancing the performance of solar cells, enhancing the optical data storage, ameliorating light extraction in LEDs, and increasing the performance of optical lenses. Bernhard first discovered the function of antireflection of moth-eye structures in the nanophotonics fields in 1967. Several methods are available for fabricating AR nanostructures, for instance, interface holographic lithography, electron-beam lithography, nanosphere lithography, anodic oxidation porous alumina and so on. Nevertheless, these methods involve expensive and sophisticated apparatus when it comes to large scale fabrication of AR film.